Presentation - Martín Viso, Iñaki (Reti Medievali Rivista, 2016)
This paper is an introduction of the monographic section about The collapse of the early medieval European kingdoms (8th-9th centuries). Firstly, the different interpretations of collapse in human societies are reviewed. Against the views which highlight the catastrophic meaning of collapses, the paper argues that the negative consequences of those deep socio-political changes were more evident for elites than for the rest of population. They were multiple-caused processes, but the key was the stress of socio-political structures. Secondly, the paper argues that the theoretical framework about the study of collapse is useful to understand the end of early medieval kingdoms during 8th and 9th centuries. However, there are a lot of possibilities. In some cases, the collapse was clear and involved a decline of socio-political complexity, like in the Visigothic kingdom or the Great Moravia. But in other cases, the collapse was not so deep and it could work as a legitimizing narration of the new order.